2017
DOI: 10.1007/s11695-017-2573-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia in Subjects Randomized into Roux-en-Y Gastric Bypass or Sleeve Gastrectomy

Abstract: The etiology of anemia appears to be iron-related and precipitated by the female sex. Scant iron supplementation is likely causative. However, anemia of chronic inflammation cannot be discounted as being somewhat causal. Subsequently, the aggregate may have had a synergistic influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 8 publications
2
35
2
Order By: Relevance
“…In a meta‐analysis of studies of the prevalence of anaemia and nutritional deficiencies following RYGB vs SG, no procedural differences in rates of anaemia and iron deficiency were observed . In a study of 100 diabetics randomized to RYGB vs SG (STAMPEDE study), anaemia was in fact more prevalent at 2, 3, and 4 years after SG . These findings suggest that the preserved duodenum and proximal jejunum in SG do not appear to reduce the risk for postoperative iron deficiency or anaemia.…”
Section: Postoperative Iron Nutritionmentioning
confidence: 95%
“…In a meta‐analysis of studies of the prevalence of anaemia and nutritional deficiencies following RYGB vs SG, no procedural differences in rates of anaemia and iron deficiency were observed . In a study of 100 diabetics randomized to RYGB vs SG (STAMPEDE study), anaemia was in fact more prevalent at 2, 3, and 4 years after SG . These findings suggest that the preserved duodenum and proximal jejunum in SG do not appear to reduce the risk for postoperative iron deficiency or anaemia.…”
Section: Postoperative Iron Nutritionmentioning
confidence: 95%
“…Our initial search identified a total of 5234 potentially relevant citations. Following screening, a total of 49 studies with 12,880 patients were eligible for inclusion 4,6,21–67 . Of these, five were randomized controlled trials, 33 were retrospective cohort studies, 10 were prospective cohort studies, and one was a nested case–control study.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies compared outcomes in patients who received iron supplementation with those who did not 29,31,36,40,43,63 . Of these, five found that patients who took iron supplementation were less likely to develop ID and IDA compared with those who did not 29,31,36,40,63 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, premenopausal women are highly diagnosed with anemia postoperatively. Another study suggested that women are at a higher risk of eating less than men, although with limited evidence, which may add other risk for iron deficiency anemia[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the net effects observed as a result of the adaptation of bariatric surgery may synergistically affect the hemoglobin level. These complicated factors include reduction of inflammation, adaptation of micronutrient absorption, limited meat intake, attenuated energy intake, and menstruation[ 12 , 13 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%